Regulation of OPA1 processing and mitochondrial fusion by m-AAA protease isoenzymes and OMA1 - Ehses, Sarah (The Rockefeller University Press, 2009)
Mitochondrial fusion depends on the dynamin-like guanosine triphosphatase OPA1, whose activity is controlled by proteolytic cleavage. Dysfunction of mitochondria induces OPA1 processing and results in mitochondrial fragmentation, allowing the selective removal of damaged mitochondria. In this study, we demonstrate that two classes of metallopeptidases regulate OPA1 cleavage in the mitochondrial inner membrane: isoenzymes of the adenosine triphosphate (ATP)–dependent matrix AAA (ATPase associated with diverse cellular activities [m-AAA]) protease, variable assemblies of the conserved subunits paraplegin, AFG3L1 and -2, and the ATP-independent peptidase OMA1. Functionally redundant isoenzymes of the m-AAA protease ensure the balanced accumulation of long and short isoforms of OPA1 required for mitochondrial fusion. The loss of AFG3L2 in mouse tissues, down-regulation of AFG3L1 and -2 in mouse embryonic fibroblasts, or the expression of a dominant-negative AFG3L2 variant in human cells decreases the stability of long OPA1 isoforms and induces OPA1 processing by OMA1. Moreover, cleavage by OMA1 causes the accumulation of short OPA1 variants if mitochondrial DNA is depleted or mitochondrial activities are impaired. Our findings link distinct peptidases to constitutive and induced OPA1 processing and shed new light on the pathogenesis of neurodegenerative disorders associated with mutations in m-AAA protease subunits.